ORDERING INFORMATION SYSTEM INTO HALF OF WOOD WOOD PROCESSING IN PT. HARAPAN JAYA - Azis Dahlan; Irwan Bastian, SKom, MMSI (Jurnal Sistem Informasi, 2002)
With the formation of the data processing system on the sale of PT. Harapan Jayacomputerized, is a step forward in realizing the work activities that require speed andaccuracy that can be realized quality service to customers, primarily in the salesinvoice.